1964
DOI: 10.1115/1.3653066
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Head Breakdown in Cavitating Inducers

Abstract: The mechanism of head breakdown in cavitating inducers, as affected by thermodynamic properties of the pump fluid and scale effects, is discussed. The approach taken by other investigators is presented, and the limitations to cavitation scaling are examined in relation to experimental data. Because of the incomplete correlation with test data observed, a hypothesis is introduced which relates the head breakdown process to an acoustic shock phenomenon at the point of the leading-edge blade cavity collapse. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Finally, we should mention one other process that may be at work in the closure region. In the case of predominantly vapor-filled cavities Jakobsen (1964) has suggested that a condensation shock provides a mechanism for cavity closure (simple shocks of this kind were analysed in Section 6.9). This last suggestion deserves more study than it has received to date.…”
mentioning
confidence: 99%
“…Finally, we should mention one other process that may be at work in the closure region. In the case of predominantly vapor-filled cavities Jakobsen (1964) has suggested that a condensation shock provides a mechanism for cavity closure (simple shocks of this kind were analysed in Section 6.9). This last suggestion deserves more study than it has received to date.…”
mentioning
confidence: 99%
“…The velocity of the reentrant motion is estimated about V j = 13.4 m/s ± 1.2 m/s from the slope of the line C as just mentioned before. The velocity V s at an attached cavity surface, on the other hand, was approximated by Jakobsen [12] based on the Bernoulli's theorem as follow,…”
Section: Image Analysis Results For Unsteady Behavior Of Cloud Cavitamentioning
confidence: 99%
“…Kawanami et al [11] reported that an obstacle was installed on a hydrofoil surface to stop the reentrant motion from flowing toward its leading edge and obtained the result on the suppression of a large cloud shedding and the reduction of cavitation noise. However, some researchers suggested that there can be other mechanisms for the reentrant motion, such as existence of a condensation shock [12] and a collapse of cloud with a shock wave [13]. Thus the cause of the reentrant motion has yet to be completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the speed of sound in a two-phase mixture is about a hundred or a thousand times smaller than in pure vapor or liquid, respectively. 35 In order to better understand the behavior of the cavitating turbulent structures, it was necessary to discriminate the compressibility effect and the vapor phase effects. For this reason, the present study attempts to compare the compressibility effect on one-phase supersonic mixing layers to that on this cavitating mixing layer.…”
Section: B Cavitating Shear Layermentioning
confidence: 99%